2021
DOI: 10.3390/foods10081745
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anthocyanin Profiles in Various Blackcurrant Cultivars over a Three-Year Period Using a Fast HPLC-DAD Method

Abstract: Anthocyanins are the most important polyphenolic substances contained in blackcurrant fruits. They are responsible for the various health benefits caused, in particular, by their high antioxidant activity. Anthocyanins derived from anthocyanidins cyanidin and delphinidin are typical for blackcurrant fruits, especially their rutinoside and glucoside forms. These four anthocyanins usually represent about 97–98% of total anthocyanins in blackcurrant fruits. In this study, we developed and validated a new HPLC-DAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…For these reasons, the value observed using a pH-differential method would be lower than that which had been obtained using HPLC analysis. Accordingly, this determination is in line with what has been reported in various published articles [25][26][27]. Several studies have suggested that anthocyanins could effectively ameliorate the liver injuries caused by APAP administration in rats and mice through the inhibition of lipid peroxidation, improved GSH depletion, and by inducing antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…For these reasons, the value observed using a pH-differential method would be lower than that which had been obtained using HPLC analysis. Accordingly, this determination is in line with what has been reported in various published articles [25][26][27]. Several studies have suggested that anthocyanins could effectively ameliorate the liver injuries caused by APAP administration in rats and mice through the inhibition of lipid peroxidation, improved GSH depletion, and by inducing antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…Dietary intervention with BC significantly reduced the increased concentration of TBARS, 7-KCh, and LOOHs in the testes of rats exposed to DEE. These results are in line with previous studies, showing the protective effects of anthocyanins from blackcurrants against oxidative stress and other redox-related responses [ 83 , 84 ]. Our results showed the high concentrations of anthocyanins in blackcurrant pomace, mainly cyanidin-3-glucoside, delphinidin-3-O-glucoside, cyanidin-3-O-rutinoside, and delphinidin-3-O-rutinoside ( Supplementary Materials ), which possess the ROS-scavenging activity against hydroxyl radicals and superoxide, and metal-chelating abilities in vitro and in vivo [ 22 , 85 , 86 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, anthocyanins were extracted and characterized using HPLC‐mass spectrometry (HPLC‐MS) from different genotypes. HPLC‐MS is a sensitive method for quantifying the anthocyanins in samples (Šimerdová et al, 2021). Data generated from the present study allowed us to compare the enzyme activities, anthocyanin contents, and correlation between these traits.…”
Section: Discussionmentioning
confidence: 99%